Evidence of integumentary scale diversity in the late Jurassic Sauropod Diplodocus sp. from the Mother’s Day Quarry, Montana - Tess Gallagher; Jason Poole; Jason P. Schein (PeerJ, 2021)
The life appearance of dinosaurs is a hotly debated topic in the world of paleontology, especially when it comes to dinosaur integument. In the case of sauropods, however, the topic is harder to properly discuss due to the limited amount of fossilized skin impressions that have been discovered. Thus far, the fossil record of sauropod integument fossils include titanosaur embryos from Patagonia, possible keratinous diplodocid dorsal spines, track ways with foot impressions, and other isolated skin impressions found in association with sauropod body fossils. Several prominent integument fossils have been found at the Mother’s Day Quarry, located in the Bighorn Basin, Montana. These discoveries may bring new important information about diplodocids, specifically Diplodocus sp. Here we describe newly uncovered fossilized skin that gives evidence of scale diversity in the genus Diplodocus. The scales themselves represent tubercles, and exhibit various shapes including rectangular, ovoid, polygonal, and globular scales. The tubercles are small in size, the biggest of which only reach about 10mm in length. Considering how diverse the scale shapes are in such a small area of skin, it is possible that these distinct scale shapes may represent a transition on the body from one region to another: perhaps from the abdomen to dorsal side, or abdomen to shoulder. Based on analysis of extant integument and scale orientation of crocodilians, it is possible to hypothesize on the location of the integument relative to the body as well as the size and relative maturational status of the individual.